The Implementation of Learning Medium: Google Meet Application for ELE Students in EFL Distance Learning - Ketut Ari Setyawati; Ni Luh Putu Era Adnyayanti (Jurnal Sinestesia, 2022)
The emergence of Covid-19 changed face-to-face learning into online learning. Those conditions required a platform or learning medium in facilitating the learning process. Learning medium in online learning became the one consideration in the online learning to have a virtual meeting. One of the applications that can provide virtual meetings is Google Meet. GM provides features that support distance learning run well. Therefore, the current research aimed to explore the implementation of using Google Meet as an online medium in the EFL distance learning at the Ganesha University of Education. The research employs descriptive qualitative research which gains the data through observations and interviews for three days during the learning process. The results of the research found that Google Meet can be an effective learning medium to use in distance learning. There are many advantages obtained such as, students more understanding the material, can meet a face-to-face virtual meeting, and many features to support virtual meeting. However, that is a barrier like requiring a good internet connection.